1994
DOI: 10.1007/bf00198186
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma with tumor thrombus in the inferior vena cava and right atrium

Abstract: Tumor thrombus (TT) in the inferior vena cava (IVC) and right atrium (RA) is rarely encountered. We have diagnosed before death and treated a case of hepatocellular carcinoma (HCC) with TT in the IVC and RA, accompanied by a brain metastasis. The image characteristics on computed tomography (CT), magnetic resonance imaging (MRI), and conventional angiography are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…Se ha descrito igualmente la invasión metastásica de la vena cava inferior y de la aurícula derecha (4)(5)(6)(7)(8). En pacientes con hepatocarcinoma, las metástasis en aurícula derecha como resultado de la invasión directa y extensión a través de la vena cava inferior son extremadamente infrecuentes (9,10).…”
Section: Discussionunclassified
“…Se ha descrito igualmente la invasión metastásica de la vena cava inferior y de la aurícula derecha (4)(5)(6)(7)(8). En pacientes con hepatocarcinoma, las metástasis en aurícula derecha como resultado de la invasión directa y extensión a través de la vena cava inferior son extremadamente infrecuentes (9,10).…”
Section: Discussionunclassified
“…Inhomogeneous enhancement is seen on late Gd imaging (j-l). Note the presence of multiple, nodular pulmonary lesions, representing pulmonary metastases (arrows, b) b e.g., adrenocortical carcinoma (Ritchey et al 1987;Godine et al 1990), hepatocellular carcinoma (Kanematsu et al 1994), Wilms' tumor (Gibson et al 1990), renal cell carcinoma (Paul et al 1975), recurrent pheochromocytoma (Rote et al 1977), endometrial stromal carcinoma (Phillips et al 1995), and thyroid carcinoma (Thompson et al 1978). Its presence is potentially hazardous because it can cause caval obstruction, extension of the tumor thrombus into the right atrium causing atrial occlusion, and tumor embolization.…”
Section: Venous Extensionmentioning
confidence: 99%
“…Tumor emboli have and the development of an endothelial cell lining are likely to help tumor thrombi become established within the vascular been observed in the circulation of patients with various types of cancer. [15][16][17][23][24][25] Circulating tumor emboli occur most lumen. However, the presence of necrotic thrombo-emboli within the pulmonary vessels suggested that adherence to commonly in patients with renal carcinoma and HCC, which reflects the propensity of these tumors to invade local venous the vascular wall and endothelialization were not sufficient for their survival.…”
Section: Aid Hepa 0034mentioning
confidence: 99%
“…Intravenous tumor expansion was frequently accompanied by the appearance of CD31-positive been linked to the propensity of these tumors to invade local microvessels within the tumor thrombi and fibrous perivascu-venous structures. [14][15][16][17] In rodent models, the cellular and lar thickening, giving rise to isolated tumor nodules within biochemical aspects of hepatocarcinoma genesis have been the portal areas. Intravascular expansion of disseminating studied extensively.…”
mentioning
confidence: 99%